The COVID-19 Trial Finder. (14th December 2020) - Sun, Yingcheng; Butler, Alex; Lin, Fengyang; Liu, Hao; Stewart, Latoya A; Kim, Jae Hyun; Idnay, Betina Ross S; Ge, Qingyin; Wei, Xinyi; Liu, Cong; Yuan, Chi; Weng, Chunhua
Abstract: Clinical trials are the gold standard for generating reliable medical evidence. The biggest bottleneck in clinical trials is recruitment. To facilitate recruitment, tools for patient search of relevant clinical trials have been developed, but users often suffer from information overload. With nearly 700 coronavirus disease 2019 (COVID-19) trials conducted in the United States as of August 2020, it is imperative to enable rapid recruitment to these studies. The COVID-19 Trial Finder was designed to facilitate patient-centered search of COVID-19 trials, first by location and radius distance from trial sites, and then by brief, dynamically generated medical questions to allow users to prescreen their eligibility for nearby COVID-19 trials with minimum human computer interaction. A simulation study using 20 publicly available patient case reports demonstrates its precision and effectiveness.